MODEL OF CREATION OF BATTLE ORDER FOR PERFORMING TASKS ON PROTECTION OF CRITICAL INFRASTRUCTURE FACILITIES FROM AIR ATTACK MEANS - Lapchuk, Dmytro; Onopriienko, Oleksandr (Honor and Law, 2025)
An analysis and modeling of organizational structures, processes, and methods for the employment of mobile fire groups to ensure the protection of critical infrastructure facilities have been conducted. The findings make it possible to strengthen the scientific foundation and improve the effectiveness of command and control over defensive operations, ensure their compliance with current challenges in the field of military security, and enhance the level of readiness for rapid response under conditions of high-intensity combat operations. A hypothesis for the organization of the deployment of mobile fire groups has been created. The limitations and assumptions of the model are presented. Methods for occupying firing positions have been developed depending on the level of threat and available resources.